Oral Dysbiosis Is Associated with the Pathogenesis of Aortic Valve Diseases - Erika Yaguchi; Yuske Komiyama; Shu Inami; Ikuko Shibasaki; Tomoaki Shintani; Ryo Shiraishi; Toshiki Hyodo; Hideki Shiba; Shinsuke Hamaguchi; Hirotsugu Fukuda; Shigeru Toyoda; Chonji Fukumoto; et al. (Microorganisms)
The involvement of oral bacteria in the pathogenesis of distant organs, such as the heart, lungs, brain, liver, and intestine, has been shown. We analyzed the distribution of bacterial species in the resected aortic valve by 16S rRNA metagenomic analysis and directly compared their gene sequences with those in the oral cavity. Thirty-two patients with aortic stenosis or aortic regurgitation who underwent aortic valve replacement were enrolled in this study. Antibody titer against periodontal pathogenic bacteria in the patient’s serum was analyzed. The genetic background and distribution of bacterial species on subgingival plaque, the dorsal surface of the tongue, and the resected aortic valve were analyzed. Patients with aortic valve disease were shown to have more severe periodontal disease by the detection of antibodies against Socransky’s red-complex bacteria of periodontitis. Bacterial DNA was detected in the aortic valves of 12 out of 32 patients. The genomic sequences of the V3-V4 region of the 16S rRNA in some bacteria isolated from the aortic valves of six patients who underwent metagenomic analysis were identical to those found in the oral cavity. The findings indicate that bacteria detected in the aortic valve may be introduced through oral dysbiosis, a condition characterized by an imbalance in the oral microbiota that increases the risk of periodontal disease and dental caries. Oral dysbiosis and the resulting potential bacteremia are associated with the pathogenesis of aortic valve diseases.